THE EFFECT OF CREDIT GROWTH ON CREDIT RISK AT REGIONAL DEVELOPMENT BANKS IN INDONESIA - Vicia Dwiartha Rini; Lenny Suardi (SEAN Institute, 2023)
Credit risk is an important indicator in determining the health of a bank. This study aims to investigate the impact of credit growth on credit risk in Regional Development Banks in Indonesia. This research uses panel data regression methods on 21 Regional Development Banks in Indonesia for the period from 2011 to 2021, with data sourced from the annual financial reports of each bank. The results of the data analysis show that credit growth significantly affects credit risk. This study can provide information on the impact of the phenomenon of credit growth on credit risk in Regional Development Banks in Indonesia, which becomes the basis of information and policy consideration in optimizing credit levels and the depiction of credit risk in Regional Development Banks.